Active energy ray-curable resin composition, pressure-sensitive adhesive composition, and pressure-sensitive adhesive
Patent Information
- Application Number
- JP2021010887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-27
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-01-27
AI Technical Summary
【0011】 本発明の活性エネルギー線硬化性樹脂組成物は、環境対応に適したものでありながらも、粘着剤を調製した際に良好な粘着力を有するものである。本発明の活性エネルギー線硬化性樹脂組成物は、例えば、コーティング剤、塗料、インキ、粘着剤など、各種の用途に適用できる。本発明の活性エネルギー線硬化性樹脂組成物は、殊に粘着剤組成物として利用することが好ましく、この粘着剤組成物を硬化させてなる粘着剤が好適である。
Smart Images

Figure 0007639361000001 
Figure 0007639361000002 
Figure 0007639361000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable resin composition, an adhesive composition, and an adhesive, and more specifically, to an active energy ray-curable resin composition that contains a urethane (meth)acrylate compound made from raw materials derived from plants and has good adhesive strength when an adhesive is prepared, an adhesive composition comprising this resin composition, and an adhesive obtained by curing this adhesive composition. [Background technology]
[0002] Conventionally, urethane (meth)acrylate compounds obtained by reacting diol compounds such as polyester diol and polyether diol, diisocyanate compounds such as isophorone diisocyanate and diphenylmethane diisocyanate, and hydroxyl group-containing (meth)acrylate compounds such as hydroxyethyl acrylate have been known as active energy ray-curable resin compositions, and are used for applications such as pressure sensitive adhesives, paints, coating agents, and adhesives.
[0003] However, most urethane (meth)acrylate compounds are composed of petroleum-derived raw materials, and do not currently take into consideration environmental issues such as global warming. In addition, research into urethane (meth)acrylate compounds using plant-derived raw materials is also being actively conducted, and urethane (meth)acrylate compounds using polyester polyols using dimer acids, which are plant-derived raw materials, have been proposed (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-43636 [Patent Document 2] Japanese Patent Application Publication No. 5-262848 [Patent Document 3] Japanese Patent Application Publication No. 10-330453 [Patent Document 4] JP 2010-100711 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the active energy ray-curable resin compositions containing urethane (meth)acrylate compounds described in the above Patent Documents 1 to 4 take environmental issues into consideration, the adhesives prepared therewith have poor adhesive strength, and therefore further improvements are required from the viewpoint of achieving both environmental friendliness and adhesive properties.
[0006] Under these circumstances, the present invention aims to provide an active energy ray-curable resin composition that contains a urethane (meth)acrylate compound made from raw materials derived from plants and has good adhesive strength when an adhesive is prepared, an adhesive composition comprising this resin composition, and an adhesive obtained by curing this composition. [Means for solving the problem]
[0007] However, as a result of intensive research to solve the above problems, the present inventors have found that in an active energy ray-curable resin composition containing a urethane (meth)acrylate compound (A) and an ethylenically unsaturated monomer (B) having a number average molecular weight in a specific range obtained using raw materials derived from plants, by setting the glass transition temperature of the cured product (I) when prepared from the active energy ray-curable resin composition to a temperature range higher than usual, the cured product (I) is environmentally friendly while having good adhesive strength when prepared into an adhesive, and have completed the present invention.
[0008] That is, the gist of the present invention is an active energy ray-curable resin composition which contains a urethane (meth)acrylate compound (A) having a number average molecular weight of 1500 to 23000, which is a reaction product of a polyester polyol (a1) containing a structural portion derived from a dimer acid, a polyisocyanate (a2) and a hydroxyl group-containing (meth)acrylate (a3), and which contains an ethylenically unsaturated monomer (B), wherein the glass transition temperature of a cured product (I) of the active energy ray-curable resin composition exceeds 30°C, and 70 The active energy ray-curable resin composition is characterized in that the viscosity is 0.05 to 1.0 MPa.
[0009] Another aspect of the present invention is a pressure-sensitive adhesive composition comprising the active energy ray-curable resin composition, and a pressure-sensitive adhesive obtained by curing the pressure-sensitive adhesive composition.
[0010] In the present invention, as the raw material of the urethane (meth)acrylate compound (A), generally plant-derived materials such as dimer acid and dimer diol can be used. The plant-derived raw material may contain impurities, and if the molecular weight of the urethane (meth)acrylate compound (A) is large, the impurities may cause gelation or adversely affect the adhesive properties. Therefore, when trying to obtain a urethane (meth)acrylate compound with a large number average molecular weight, there is a tendency to avoid using plant-derived raw materials such as dimer acid and dimer diol. However, in the present invention, in order to maintain environmental compatibility by using plant-derived raw materials, the number average molecular weight of the urethane (meth)acrylate compound (A) can be increased while using dimer acid and dimer diol, so that the adhesive strength can be improved. Effect of the Invention
[0011] The active energy ray curable resin composition of the present invention is suitable for environmental compatibility, and has good adhesive strength when prepared into an adhesive. The active energy ray curable resin composition of the present invention can be applied to various applications, such as coating agents, paints, inks, and adhesives. The active energy ray curable resin composition of the present invention is particularly preferably used as an adhesive composition, and an adhesive obtained by curing this adhesive composition is suitable. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, however, these are examples of preferred embodiments and the present invention is not limited to these. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively.
[0013] [Active energy ray-curable resin composition] The active energy ray-curable resin composition of the present invention contains a urethane (meth)acrylate compound (A) and an ethylenically unsaturated monomer (B), and further contains a photopolymerization initiator (C) as required. Each component will be described below.
[0014] <Urethane (meth)acrylate compound (A)> The urethane (meth)acrylate compound (A) in the present invention is a reaction product of a polyester polyol (a1) containing a structural portion derived from a dimer acid, a polyisocyanate (a2) and a hydroxyl group-containing (meth)acrylate (a3), and has a number average molecular weight of 1,500 to 23,000.
[0015] [Polyester polyol (a1) containing a structural portion derived from dimer acid] Examples of the polyester polyol (a1) containing a structural portion derived from a dimer acid (hereinafter, the polyester polyol (a1) containing a structural portion derived from a dimer acid will be simply referred to as "polyol (a1)") include (1) one obtained by a polycondensation reaction between a dimer acid and a polyhydric alcohol, or (2) one obtained by a polycondensation reaction between a dimer diol obtained by reducing a dimer acid and a polyvalent carboxylic acid, and among these, (1) is preferred in terms of ease of availability.
[0016] Examples of the dimer acid include thermal dimers of unsaturated fatty acids and hydrogenated dimer acids obtained by hydrogenating the same. Specifically, the dimers are mainly composed of unsaturated fatty acids having 10 to 24 carbon atoms, preferably about 18 carbon atoms, and are dicarboxylic acids derived from unsaturated fatty acids such as oleic acids, linoleic acids, linolenic acids, and erucic acids. Main dimer acids include those having 36 and 44 carbon atoms.
[0017] The polyhydric alcohol that undergoes a polycondensation reaction with the dimer acid is an alcohol having a number of hydroxyl groups, i.e., a valence of 2 or more, and the valence is preferably 2 to 6, and more preferably 2 or 3. Examples of the polyhydric alcohol include aliphatic or alicyclic polyhydric alcohols having 2 to 40 carbon atoms. Specific examples of the polyhydric alcohol include linear polyhydric alcohols having 2 to 20 carbon atoms, such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, and 1,20-eicosanediol; 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, and the like. polyhydric alcohols having a branched chain and having 4 to 40 carbon atoms, such as 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, etc.; polyhydric alcohols having a cyclic structure in the molecule and having 4 to 20 carbon atoms, such as 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, etc.; diethylene glycol, triethylene glycol, polytetramethylene ether glycol, dimer diol, etc. One type selected from these polyhydric alcohols may be used alone, or two or more types may be used in combination. Among them, from the viewpoints of availability and adhesive strength when an adhesive is prepared, linear polyhydric alcohols having 2 to 10 carbon atoms, particularly 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol, and branched polyhydric alcohols having 4 to 10 carbon atoms, particularly neopentyl glycol, are preferably used.
[0018] That is, the polyol (a1) is a polycondensate of a dimer acid and a glycol, and the glycol is particularly preferably at least one glycol selected from the group consisting of 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol.
[0019] In addition, the polyvalent carboxylic acid that undergoes polycondensation reaction with the dimer diol as an acid component other than the dimer acid is a carboxylic acid having a number of carboxy groups, i.e., a valence of 2 or more, and the valence is preferably 2 or 3. Examples of dicarboxylic acids having a valence of 2 among the polyvalent carboxylic acids include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, trimellitic acid, and furandicarboxylic acid. Among these, succinic acid, adipic acid, and sebacic acid are preferably used in terms of availability and adhesive strength when an adhesive is prepared.
[0020] In the present invention, the term "carboxylic acid" includes not only carboxylic acid but also derivatives of carboxylic acid such as carboxylic acid salts, carboxylic acid anhydrides, carboxylic acid halides, and carboxylic acid esters.
[0021] In the present invention, the number average molecular weight of the polyol (a1) is preferably 800 to 5000, more preferably 1000 to 4000, particularly preferably 1500 to 3500, particularly preferably 1700 to 3300, and further preferably 1800 to 2800, from the viewpoints of handleability and adhesive strength when an adhesive is prepared. If the number average molecular weight is too small, the adhesive strength of the prepared adhesive tends to be low, whereas if it is too large, the viscosity of the polyol (a1) tends to increase, resulting in reduced handleability and reactivity.
[0022] In the present invention, the number average molecular weight is determined from the hydroxyl value, and the hydroxyl value is measured by a method using an acetylating reagent or a phthalating reagent in accordance with JIS K1557-1 (2007).
[0023] The polyol (a1) may be used alone or in combination of two or more kinds.
[0024] [Polyisocyanate (a2)] The polyisocyanate (a2) used in the present invention is an isocyanate having two or more isocyanate groups, and the number of isocyanate groups is preferably two or three. Examples of the polyisocyanate include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; alicyclic polyisocyanates such as hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; and polymeric compounds such as trimer compounds of the above polyisocyanates. Further examples include allophanate type polyisocyanates and biuret type polyisocyanates. The polyisocyanate (a2) may be used alone or in combination of two or more kinds.
[0025] Among these, in terms of adhesive properties when the adhesive is prepared, aliphatic polyisocyanates and alicyclic polyisocyanates are preferred, and isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylene diisocyanate, and hexamethylene diisocyanate are more preferred, with isophorone diisocyanate being particularly preferred.
[0026] [Hydroxyl group-containing (meth)acrylate (a3)] The hydroxyl group-containing (meth)acrylate (a3) used in the present invention is a (meth)acrylate containing one or more hydroxyl groups, and among the hydroxyl group-containing (meth)acrylates, those corresponding to the above polyol (a1) are excluded. Examples of the hydroxyl group-containing (meth)acrylate (a3) include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and 2-hydroxy-3-(meth)acryloyloxyethyl acrylate. hydroxyl-containing (meth)acrylates containing one ethylenically unsaturated group, such as oxypropyl (meth)acrylate; hydroxyl-containing (meth)acrylates containing two ethylenically unsaturated groups, such as glycerin di(meth)acrylate and 2-hydroxy-3-acryloyl-oxypropyl methacrylate; and hydroxyl-containing (meth)acrylates containing three or more ethylenically unsaturated groups, such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate. The hydroxyl group-containing (meth)acrylate (a3) may be used alone or in combination of two or more kinds.
[0027] Among these, in terms of adhesive properties when an adhesive is prepared, a hydroxyl-containing (meth)acrylate containing one ethylenically unsaturated group is preferred, and a hydroxyalkyl (meth)acrylate is further preferably used, and a hydroxyalkyl (meth)acrylate having an alkyl group with 1 to 4 carbon atoms, particularly 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate, are particularly preferred.
[0028] [Production of urethane (meth)acrylate compound (A)] The urethane (meth)acrylate compound (A) in the present invention is obtained by reacting the above components (a1) to (a3). The production method is not particularly limited, and it can be produced according to a known method. Specifically, it can be produced, for example, as follows.
[0029] For example, there may be mentioned (i) a method in which the above-mentioned polyol (a1), polyisocyanate (a2), and hydroxyl group-containing (meth)acrylate (a3) are charged into a reactor all at once or separately and reacted; (ii) a method in which the polyol (a1) and polyisocyanate (a2) are reacted in advance to obtain a terminal isocyanate group-containing reaction product, and the hydroxyl group-containing (meth)acrylate (a3) is reacted with the resulting reaction product; and (iii) a method in which the polyisocyanate (a2) and hydroxyl group-containing (meth)acrylate (a3) are reacted in advance to obtain a reaction product, and the like, and the like. From the viewpoints of reaction stability and reduction of by-products, the method (ii) is preferred.
[0030] In the above method (ii), the reaction between the polyol (a1) and the polyisocyanate (a2) can be carried out by a known reaction means. In this case, for example, the molar ratio of the isocyanate group in the polyisocyanate (a2) to the hydroxyl group in the polyol (a1) is preferably about 2n:(2n-2) (n is an integer of 2 or more), which allows the isocyanate group to remain and facilitates the addition reaction with the hydroxyl group-containing (meth)acrylate (a3).
[0031] In the above molar ratio, n is preferably 4 or more and 10 or less. The lower limit of n is more preferably 5, and particularly preferably 6. The upper limit of n is more preferably 9, particularly preferably 8, and even more preferably 7. If n is too small, the adhesive strength tends to be low when the adhesive is prepared, and if n is too large, the viscosity of the active energy ray-curable resin composition tends to increase, decreasing the handleability.
[0032] The molar reaction ratio between the terminal isocyanate group-containing reaction product and the hydroxyl group-containing (meth)acrylate (a3) is usually about 1:2 in terms of molar ratio when the terminal isocyanate group-containing reaction product has two isocyanate groups and the hydroxyl group-containing (meth)acrylate (a3) has one hydroxyl group; and when the terminal isocyanate group-containing reaction product has three isocyanate groups and the hydroxyl group-containing (meth)acrylate (a3) has one hydroxyl group, the molar reaction ratio between the terminal isocyanate group-containing reaction product and the hydroxyl group-containing (meth)acrylate compound (a3) is usually about 1:3 in terms of molar ratio.
[0033] In the addition reaction between this terminal isocyanate group-containing reaction product and the hydroxyl group-containing (meth)acrylate (a3), it is preferable to terminate the reaction when the residual isocyanate group content in the reaction system is usually 0.1% by weight or less, thereby obtaining the urethane (meth)acrylate compound (A) of the present invention.
[0034] In the present invention, in the reaction between the polyol (a1) and the polyisocyanate (a2), and further in the reaction between the terminal isocyanate group-containing reaction product obtained by the reaction and the hydroxyl group-containing (meth)acrylate (a3), it is also preferable to use a catalyst for the purpose of promoting the reaction.
[0035] Examples of such catalysts include organometallic compounds such as dibutyltin dilaurate, trimethyltin hydroxide, and tetra-n-butyltin; metal salts such as zinc octoate, tin octoate, cobalt naphthenate, stannous chloride, and stannic chloride; amine catalysts such as triethylamine, benzyldiethylamine, 1,4-diazabicyclo[2,2,2]octane, 1,8-diazabicyclo[5,4,0]undecene, N,N,N',N'-tetramethyl-1,3-butanediamine, and N-ethylmorpholine; and bismuth catalysts. Examples of bismuth catalysts include inorganic bismuth compounds such as bismuth nitrate, bismuth bromide, bismuth iodide, and bismuth sulfide; organic bismuth compounds such as dibutyl bismuth dilaurate and dioctyl bismuth dilaurate; and organic acid bismuth salts such as bismuth 2-ethylhexanoate, bismuth naphthenate, bismuth isodecanoate, bismuth neodecanoate, bismuth laurate, bismuth maleate, bismuth stearate, bismuth oleate, bismuth linoleate, bismuth acetate, bismuth tribisneodecanoate, and bismuth disalicylate. Among these, organometallic compounds and amine catalysts are preferred, and dibutyltin dilaurate and 1,8-diazabicyclo[5,4,0]undecene are more preferred.
[0036] In the reaction of the polyol (a1) with the polyisocyanate (a2) and further in the reaction of the terminal isocyanate group-containing reaction product obtained by the reaction with the hydroxyl group-containing (meth)acrylate (a3), an organic solvent that does not have a functional group that reacts with an isocyanate group, for example, an ester such as ethyl acetate or butyl acetate; a ketone such as methyl ethyl ketone or methyl isobutyl ketone; or an aromatic compound such as toluene or xylene, can be used.
[0037] The reaction temperature is usually 30 to 90° C., preferably 40 to 80° C., and the reaction time is usually 2 to 12 hours, preferably 3 to 10 hours.
[0038] Thus, the urethane (meth)acrylate compound (A) is obtained. The active energy ray-curable resin composition of the present invention may contain one type of urethane (meth)acrylate compound (A) alone, or may contain two or more types.
[0039] In the present invention, it is important that the number average molecular weight of the urethane (meth)acrylate compound (A) obtained above is 1500 to 23000, preferably 2000 to 22000, more preferably 2300 to 21000, and particularly preferably 2500 to 20000. If the number average molecular weight is too small, the adhesive strength when prepared into a pressure-sensitive adhesive tends to be low, whereas if the number average molecular weight is too large, the viscosity of the resin composition tends to increase, decreasing handleability, and problems such as gelation due to impurities contained in the plant-derived dimer acid tend to occur.
[0040] The weight average molecular weight of the urethane (meth)acrylate compound (A) is preferably 1000 to 100000, more preferably 4000 to 90000, and particularly preferably 7000 to 80000. If the weight average molecular weight is too small, the adhesive strength when prepared tends to be low, whereas if the weight average molecular weight is too large, the viscosity of the resin composition tends to increase, reducing handleability, and causing problems such as gelation due to impurities contained in the plant-derived dimer acid.
[0041] Furthermore, the degree of dispersion (weight average molecular weight / number average molecular weight) of the urethane (meth)acrylate compound (A) is preferably 15 or less, more preferably 10 or less, particularly preferably 7 or less, and even more preferably 5 or less. If the degree of dispersion is too high, the viscosity increases, the handling property decreases, and the adhesive strength tends to be insufficient. The lower limit of the degree of dispersion is usually 1.1 from the viewpoint of the production limit.
[0042] The number average molecular weight and weight average molecular weight are the number average molecular weight and weight average molecular weight converted into standard polystyrene molecular weight, and are measured by using four columns in series: ACQUITY APC XT 450 x 1, ACQUITY APC XT 200 x 1, and ACQUITY APC XT 45 x 2, in a high performance liquid chromatograph (Waters, "ACQUITY APC System"). In this case, if the measurement contains an ethylenically unsaturated monomer (B) described below, the number average molecular weight and weight average molecular weight are obtained excluding the ethylenically unsaturated monomer (B). The degree of dispersion is also determined from the weight average molecular weight and the number average molecular weight.
[0043] <Ethylenically unsaturated monomer (B)> The ethylenically unsaturated monomer (B) used in the present invention may be any monomer having one or more ethylenically unsaturated groups in one molecule, and may be a monofunctional monomer, a bifunctional monomer, or a trifunctional or higher monomer. The active energy ray curable resin composition of the present invention may contain one type of ethylenically unsaturated monomer (B) alone, or may contain two or more types.
[0044] Examples of the monofunctional monomer include styrene, vinyl toluene, chlorostyrene, α-methylstyrene, methyl (meth)acrylate, ethyl (meth)acrylate, acrylonitrile, vinyl acetate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-phenoxy-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, glycerin mono(meth)acrylate, glycidyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, ) acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, n-stearyl (meth)acrylate, benzyl (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, nonylphenol propylene oxide modified (meth)acrylate, half ester (meth)acrylate of phthalic acid derivative such as 2-(meth)acryloyloxy-2-hydroxypropyl phthalate, furfuryl (meth)acrylate, carbitol (meth)acrylate, benzyl (meth)acrylate, butoxyethyl (meth)acrylate, allyl (meth)acrylate, acryloylmorpholine, 2-hydroxyethyl acrylamide, N-methylol (meth)acrylamide, N-vinylpyrrolidone, 2-vinylpyridine, 2-(meth)acryloyloxyethyl acid phosphate monoester, and the like.
[0045] In addition to the above, the monofunctional monomer may also include Michael adducts of acrylic acid or 2-acryloyloxyethyl dicarboxylic acid monoesters. Examples of Michael adducts of acrylic acid include acrylic acid dimers, methacrylic acid dimers, acrylic acid trimers, methacrylic acid trimers, acrylic acid tetramers, and methacrylic acid tetramers. Examples of 2-acryloyloxyethyl dicarboxylic acid monoesters, which are carboxylic acids having specific substituents, include 2-acryloyloxyethyl succinic acid monoesters, 2-methacryloyloxyethyl succinic acid monoesters, 2-acryloyloxyethyl phthalic acid monoesters, 2-methacryloyloxyethyl phthalic acid monoesters, 2-acryloyloxyethyl hexahydrophthalic acid monoesters, and 2-methacryloyloxyethyl hexahydrophthalic acid monoesters. Oligoester acrylates may also be used.
[0046] Examples of the bifunctional monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide modified bisphenol A type di(meth)acrylate, propylene oxide modified bisphenol A type di(meth)acrylate, 1 ,6-hexanediol di(meth)acrylate, 1,6-hexanediol ethylene oxide modified di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, phthalic acid diglycidyl ester di(meth)acrylate, hydroxypivalic acid modified neopentyl glycol di(meth)acrylate, isocyanuric acid ethylene oxide modified diacrylate, 2-(meth)acryloyloxyethyl acid phosphate diester, etc.
[0047] Examples of the trifunctional or higher monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerin polyglycidyl ether poly(meth)acrylate, isocyanuric acid ethylene oxide modified triacrylate, ethylene oxide modified dipentaerythritol penta(meth)acrylate, ethylene oxide modified dipentaerythritol hexa(meth)acrylate, ethylene oxide modified pentaerythritol tri(meth)acrylate, ethylene oxide modified pentaerythritol tetra(meth)acrylate, and succinic acid modified pentaerythritol tri(meth)acrylate.
[0048] The ethylenically unsaturated monomer (B) preferably contains two or more kinds of ethylenically unsaturated monomers having different glass transition temperatures, and for example, preferably contains an ethylenically unsaturated monomer (B1) having a glass transition temperature of 0°C or more and 130°C or less (hereinafter referred to as "ethylenically unsaturated monomer (B1)"), and an ethylenically unsaturated monomer (B2) having a glass transition temperature of -60°C or more and less than 0°C (hereinafter referred to as "ethylenically unsaturated monomer (B2)"). That is, in the present invention, it is preferable to use in combination an ethylenically unsaturated monomer (B1) having a relatively high glass transition temperature and an ethylenically unsaturated monomer (B2) having a relatively low glass transition temperature, which makes it easier to obtain a composition having low viscosity and excellent adhesive strength.
[0049] In the present invention, the glass transition temperature of the ethylenically unsaturated monomer (B) refers to the glass transition temperature of a homopolymer prepared using the ethylenically unsaturated monomer (B), and the values described in POLYM HANDBOOK Fourth Edition, John Wiley & Sons, Inc. (1999) or "Polymer Data Handbook" edited by the Society of Polymer Science (1986) can be used. For the glass transition temperature (Tg) of a homopolymer not described in these publications, values described in other documents or product catalogs or values measured by producing a homopolymer can be used.
[0050] [Ethylenically unsaturated monomer (B1)] The ethylenically unsaturated monomer (B1) has a glass transition temperature of 0° C. or higher and 130° C. or lower, preferably 10° C. or higher and 120° C. or lower, and more preferably 20° C. or higher and 100° C. or lower. If the upper limit of the glass transition temperature of the ethylenically unsaturated monomer (B1) is too high, the adhesive strength of the obtained pressure-sensitive adhesive tends to decrease.
[0051] Examples of the ethylenically unsaturated monomer (B1) include styrene-based monomers such as styrene (100° C.); methyl (meth)acrylate (Tga=8° C., Tgm=105° C.), ethyl methacrylate (Tgm=65° C.), n-butyl methacrylate (Tgm=20° C.), isobutyl methacrylate (Tgm=48° C.), t-butyl (meth)acrylate (Tga=41° C., Tgm=107° C.), n-stearyl (meth)acrylate (Tga=3 0°C, Tgm=38°C); hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl methacrylate (Tgm=55°C) and 2-hydroxypropyl methacrylate (Tgm=26°C); amino group-containing (meth)acrylates such as dimethylaminoethyl methacrylate (Tgm=18°C) and diethylaminoethyl methacrylate (Tgm=16-24°C); isobornyl acrylate (Tga=97°C), diphenyl methacrylate (Tgm=100°C), etc. Alicyclic (meth)acrylates such as cyclopentanyl acrylate (Tga = 120°C), cyclohexyl (meth)acrylate (Tga = 15°C, Tgm = 66°C), and 3,3,5-trimethylcyclohexyl acrylate (Tga = 52°C); aromatic (meth)acrylates such as benzyl (meth)acrylate (Tga = 6°C, Tgm = 54°C); tetrahydrofurfuryl methacrylate (Tgm = 60°C), glycidyl (meth)acrylate (Tga = Examples of the (meth)acrylate monomers include heterocyclic (meth)acrylates such as (3-ethyloxetan-3-yl)methyl methacrylate (Tgm=46°C), (3-ethyloxetan-3-yl)methyl methacrylate (Tgm=2°C), and cyclic trimethylolpropane formal acrylate (Tga=27°C), and further include amide monomers such as vinyl acetate (Tg=29°C); hydroxyethyl acrylamide (Tg=98°C), and diethyl acrylamide (Tg=81°C). These may be used alone or in combination of two or more. Among them, alicyclic (meth)acrylates and heterocyclic (meth)acrylates are preferred, and isobornyl acrylate and cyclic trimethylolpropane formal acrylate are particularly preferred. The numerical value in ( ) after the name of the compound indicates the glass transition temperature. In addition, "Tga" indicates the glass transition temperature of the acrylate, and "Tgm" indicates the glass transition temperature of the methacrylate.
[0052] The content of the ethylenically unsaturated monomer (B1) is preferably 10 to 100 parts by weight, more preferably 20 to 80 parts by weight, and particularly preferably 30 to 60 parts by weight, based on 100 parts by weight of the urethane (meth)acrylate compound (A). When the content of the ethylenically unsaturated monomer (B1) is within the above range, it tends to be easy to achieve a low viscosity.
[0053] [Ethylenically unsaturated monomer (B2)] The ethylenically unsaturated monomer (B2) has a glass transition temperature of −60° C. or higher and lower than 0° C., preferably −50° C. or higher and −5° C. or lower, and more preferably −30° C. or higher and −10° C. or lower. If the lower limit of the glass transition temperature of the ethylenically unsaturated monomer (B2) is too low, the viscosity tends to be high.
[0054] Examples of the ethylenically unsaturated monomer (B2) include alkyl (meth)acrylates such as n-butyl acrylate (Tga = -56°C), isobutyl acrylate (Tga = -26°C), 2-ethylhexyl methacrylate (Tgm = -10°C), isononyl acrylate (Tga = -58°C), n-lauryl acrylate (Tga = -23°C), nonyl acrylate (Tga = -37°C), isostearyl acrylate (Tga = -18°C), and isodecyl methacrylate (Tgm = -41°C); 2-hydroxyethyl acrylate (Tga = -15°C), 2-hydroxypropyl acrylate (Tga = -7°C), 4-hydroxybutyl acrylate (Tg a = -32 ° C.) and other hydroxyl group-containing (meth)acrylates; aromatic (meth)acrylates such as phenoxyethyl acrylate (Tga = -22 ° C.); heterocyclic (meth)acrylates such as tetrahydrofurfuryl acrylate (Tga = -12 ° C.), (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl acrylate (Tga = -7 ° C.), 4-hydroxybutyl acrylate glycidyl ether (Tga = -59 ° C.); and (meth)acrylate monomers such as alkoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate (Tga = -50 ° C., Tgm = -2 ° C.) and 2-ethoxyethyl methacrylate (Tgm = -31 ° C.). These may be used alone or in combination of two or more. Among them, alkyl (meth)acrylates, aromatic (meth)acrylates, and heterocyclic (meth)acrylates are preferred, n-butyl acrylate, phenoxyethyl acrylate, and tetrahydrofurfuryl acrylate are more preferred, phenoxyethyl acrylate and tetrahydrofurfuryl acrylate are particularly preferred, and tetrahydrofurfuryl acrylate is particularly preferred. The numerical value in parentheses after the compound name indicates the glass transition temperature. "Tga" indicates the glass transition temperature of acrylates, and "Tgm" indicates the glass transition temperature of methacrylates.
[0055] The content of the ethylenically unsaturated monomer (B2) is preferably 10 to 100 parts by weight, more preferably 20 to 80 parts by weight, and particularly preferably 30 to 60 parts by weight, based on 100 parts by weight of the urethane (meth)acrylate compound (A). When the content of the ethylenically unsaturated monomer (B2) is within the above range, it tends to be easy to achieve a low viscosity.
[0056] The ratio (B1 / B2) of the ethylenically unsaturated monomer (B1) to the ethylenically unsaturated monomer (B2) is preferably 80 / 20 to 30 / 70, more preferably 70 / 30 to 35 / 65, and particularly preferably 65 / 35 to 40 / 60, by weight. When the ratio of the ethylenically unsaturated monomer (B1) to the ethylenically unsaturated monomer (B2) is within the above range, the viscosity is low and the adhesiveness to various members tends to be excellent.
[0057] The difference in glass transition temperature between the ethylenically unsaturated monomer (B1) and the ethylenically unsaturated monomer (B2) is usually 30 to 160° C., preferably 50 to 130° C., and more preferably 60 to 120° C. When the difference in glass transition temperature between the ethylenically unsaturated monomer (B1) and the ethylenically unsaturated monomer (B2) is within the above range, the composition tends to have a low viscosity and excellent adhesion to various members.
[0058] The ethylenically unsaturated monomer (B) may contain an ethylenically unsaturated monomer (B3) other than the ethylenically unsaturated monomer (B1) and the ethylenically unsaturated monomer (B2) within a range that does not impair the effects of the present invention (for example, 10% by weight or less of the ethylenically unsaturated monomer (B)). However, in the present invention, it is preferable that the ethylenically unsaturated monomer (B) consists only of the ethylenically unsaturated monomer (B1) and the ethylenically unsaturated monomer (B2).
[0059] Examples of the ethylenically unsaturated monomer (B3) include 2-ethylhexyl acrylate (Tga = -70°C), 4-hydroxybutyl acrylate (Tga = -80°C), ethyl carbitol acrylate (Tga = -67°C), ethoxydiethylene glycol acrylate (Tga = -70°C), isodecyl acrylate (Tga = -62°C), lauryl methacrylate (Tgm = -65°C), octyl acrylate (Tga = -65°C), and the like. ), iso-octyl acrylate (Tga = -70 ° C), tetradecyl methacrylate (Tgm = -72 ° C), acryloyl morpholine (Tg = 145 ° C), isopropyl acrylamide (Tg = 134 ° C), dimethylaminopropyl acrylamide (Tg = 134 ° C), 1-adamantyl methacrylate (Tgm = 250 ° C), 1-adamantyl acrylate (Tga = 153 ° C), acrylamide (Tg = 153 ° C), etc. These may be used alone or in combination of two or more. The numbers in ( ) after the compound name indicate the glass transition temperature. Also, "Tga" indicates the glass transition temperature of acrylate, and "Tgm" indicates the glass transition temperature of methacrylate.
[0060] The content of the ethylenically unsaturated monomer (B) is preferably 20 to 150 parts by weight, more preferably 50 to 120 parts by weight, and particularly preferably 70 to 100 parts by weight, relative to 100 parts by weight of the urethane (meth)acrylate compound (A). When the content of the ethylenically unsaturated monomer (B) is within the above range, the viscosity is low and the adhesiveness to various members tends to be excellent.
[0061] <Photopolymerization initiator (C)> The active energy ray-curable resin composition of the present invention preferably further contains a photopolymerization initiator (C) in order to more efficiently carry out curing with active energy rays.
[0062] Examples of the photopolymerization initiator (C) include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)-phenyl-(2-hydroxy-2-propyl) ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy- 2-Methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, 2,2-dimethoxy-1,2-diphenylethane-1-one, phenylglyoxylic acid methyl ester and other acetophenones; benzyl Benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone, o-benzoyl methyl benzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo benzophenones such as (4-benzoylbenzyl)trimethylammonium chloride, (2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride, and other thioxanthones;Examples of the photopolymerization initiator (C) include acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and oxime esters such as 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyloxime) and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). These photopolymerization initiators (C) may be used alone or in combination of two or more kinds.
[0063] In addition, it is also possible to use these auxiliary agents in combination with triethanolamine, triisopropanolamine, 4,4'-dimethylaminobenzophenone (Michler's ketone), 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and the like.
[0064] Among these, it is preferable to use benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, benzoin isopropyl ether, 4-(2-hydroxyethoxy)-phenyl(2-hydroxy-2-propyl) ketone, and 2-hydroxy-2-methyl-1-phenylpropan-1-one.
[0065] The content of the photopolymerization initiator (C) is preferably 0.1 to 40 parts by weight, more preferably 0.5 to 20 parts by weight, and particularly preferably 1 to 10 parts by weight, relative to 100 parts by weight of the total of the urethane (meth)acrylate compound (A) and the ethylenically unsaturated monomer (B). When the content of the photopolymerization initiator (C) is within the above range, curing by active energy rays can be carried out more efficiently. If the content of the photopolymerization initiator (C) is too high, the solution stability tends to decrease, such as precipitation during coating, and problems such as embrittlement and coloring tend to occur.
[0066] In addition, in producing the active energy ray curable composition obtained by the present invention, the mixing method of the urethane (meth)acrylate compound (A), the ethylenically unsaturated monomer (B), and the photopolymerization initiator (C) is not particularly limited, and can be mixed by various methods. For example, each component can be mixed at once, or an arbitrary component can be mixed first and then the remaining components can be mixed, and the like.
[0067] Thus, the active energy ray-curable resin composition of the present invention is obtained. If necessary, additives such as a surface conditioner, a leveling agent, a polymerization inhibitor, etc. can be further blended. When the active energy ray curable resin composition of the present invention contains an additive, the content of the additive is usually 20% by weight or less, preferably 10% by weight or less, more preferably 5% by weight or less.
[0068] The surface conditioner is not particularly limited, and examples thereof include alkyd resins. Such an alkyd resin has the effect of imparting film-forming properties during coating and the effect of increasing adhesion to a thin metal film surface.
[0069] As the leveling agent, any known leveling agent can be used as long as it has the effect of imparting wettability to the substrate and reducing surface tension to the coating liquid, such as silicone-modified resins, fluorine-modified resins, alkyl-modified resins, etc. These may be used alone or in combination of two or more kinds.
[0070] Examples of the polymerization inhibitor include p-benzoquinone, naphthoquinone, toluquinone, 2,5-diphenyl-p-benzoquinone, hydroquinone, 2,5-di-t-butylhydroquinone, methylhydroquinone, methoxyphenol, 2,6-di-t-butyl-p-cresol, mono-t-butylhydroquinone, and pt-butylcatechol. Among these, methoxyphenol and 2,6-di-t-butyl-p-cresol are preferable. These may be used alone or in combination of two or more kinds.
[0071] The active energy ray-curable resin composition of the present invention is applied onto various substrates, dried, and then cured by irradiating with active energy rays.
[0072] The method for applying the active energy ray-curable resin composition is not particularly limited, and examples thereof include wet coating methods such as spray, shower, dipping, roll, spin, curtain, flow, slit, die, gravure, comma, dispenser, screen printing, and inkjet printing.
[0073] Examples of substrates to which the active energy ray-curable resin composition obtained by the present invention is applied include polyolefin resins, polyester resins, polycarbonate resins, acrylonitrile butadiene styrene copolymers (ABS), polystyrene resins, polyamide resins, and the like, and molded products thereof (films, sheets, cups, and the like), metal substrates (metal vapor deposition layers, metal plates (copper, stainless steel (SUS304, SUSBA, and the like), aluminum, zinc, magnesium, and the like)), glass, and composite substrates thereof, and the like.
[0074] In the above coating, an organic solvent may be blended as necessary to adjust the viscosity, and examples of such organic solvents include alcohols such as methanol, ethanol, propanol, n-butanol, and i-butanol; ketones such as acetone, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone; cellosolves such as ethyl cellosolve; aromatics such as toluene and xylene; glycol ethers such as propylene glycol monomethyl ether; acetates such as methyl acetate, ethyl acetate, and butyl acetate; diacetone alcohol, etc. These organic solvents may be used alone or in combination of two or more.
[0075] In addition, when the active energy ray-curable resin composition is a solid or a high-viscosity liquid, a hot melt method in which the active energy ray-curable resin composition is heated to reduce the viscosity and then coated by the above method may be used.
[0076] Examples of such active energy rays include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, and infrared rays; electromagnetic waves such as X-rays and gamma rays; and electron beams, proton beams, and neutron beams. Curing by ultraviolet irradiation is advantageous in terms of curing speed, availability of irradiation equipment, and cost. When electron beam irradiation is performed, curing can be achieved without using a photopolymerization initiator (C).
[0077] For example, in the method of curing by ultraviolet irradiation, a device that emits light in the wavelength range of 150 to 450 nm, such as a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a xenon lamp, a chemical lamp, an electrodeless discharge lamp, or an LED, is used, and the curing rate is 30 to 3,000 mJ / cm. 2 A method of irradiating the area to a certain degree is given. After the ultraviolet irradiation, heating may be carried out as necessary to ensure complete curing.
[0078] The thickness of the cured coating film is usually 1 to 300 μm, preferably 2 to 250 μm, and more preferably 5 to 200 μm, in consideration of light transmission so that the photopolymerization initiator (C) can react uniformly.
[0079] <Cured product of active energy ray-curable resin composition (I)> As described above, the active energy ray-curable resin composition of the present invention is cured by irradiation with active energy rays to form a cured product (I). In the present invention, the glass transition temperature of the cured product (I) of the active energy ray-curable resin composition is more than 30° C. and not more than 85° C., preferably 31 to 80° C., more preferably 31 to 70° C., and particularly preferably 31 to 50° C. If the glass transition temperature (Tg) is outside the above range, the adhesive strength tends to decrease when the adhesive is prepared. Methods for producing a cured product (I) having a Tg exceeding 30°C include (1) a method for adjusting the Tg by changing the molecular weight of the urethane (meth)acrylate, and (2) a method for adjusting the Tg by changing the blending ratio of various components.
[0080] The glass transition temperature (Tg) is measured as follows. The active energy ray-curable resin composition was applied to an easily adhesive-treated polyethylene terephthalate (PET) film (thickness 125 μm) using an applicator so that the film thickness after curing would be 100 μm, and the applied film was then irradiated with a tabletop UV irradiation device (manufactured by iGraphics, "Conveyor-type tabletop irradiation device") at 80 W / cm (high pressure mercury lamp) × 18 cmH × 1.9 m / min × 3 Pass (cumulative irradiation amount 2,400 mJ / cm 2 ) and harden it to prepare an adhesive sheet for measuring adhesive strength. A test piece measuring 20 mm in length and 3 mm in width is cut out from this adhesive sheet for measuring adhesive strength. The test piece is measured using a dynamic viscoelasticity measuring device "DVA-225" manufactured by IT Measurement & Control Co., Ltd. in tension mode at a frequency of 1 Hz, a heating rate of 3°C / min, and a strain of 0.1%. The ratio (tan δ) of the imaginary part (loss modulus) to the real part (storage modulus) of the obtained complex modulus is calculated, and the maximum peak temperature of this tan δ is taken as the glass transition temperature (°C).
[0081] The gel fraction of the cured active energy ray curable resin composition is preferably 10% by weight or more, more preferably 20 to 95% by weight, particularly preferably 30 to 90% by weight, and even more preferably 40 to 85% by weight, from the viewpoints of durability and adhesive strength. If the gel fraction is too low, the cohesive strength decreases, and durability tends to decrease. However, if the gel fraction is too high, there is a concern that the adhesive strength decreases due to the increase in cohesive strength.
[0082] The gel fraction is an indication of the degree of crosslinking, and is calculated, for example, by the following method. A cured coating sheet (without a separator) formed by forming a cured coating on a polymer sheet (e.g., a PET film, etc.) as a substrate is wrapped in a 200-mesh SUS wire netting and immersed in toluene at 23°C for 24 hours. The gel fraction is the weight percentage of the insoluble cured coating component remaining in the wire netting after immersion relative to the weight of the cured coating component before immersion. The weight of the cured coating component before and after immersion is the value obtained by subtracting the weight of the substrate from the measured weight.
[0083] The active energy ray curable resin composition of the present invention can be made from a plant-derived dimer acid as a raw material, and is an active energy ray curable resin composition with reduced environmental impact. The biomass ratio can be expressed by the ratio of carbon numbers derived from plants to the total carbon contained in the active energy ray curable resin composition, and is preferably 30C% (C% represents the ratio of carbon) or more, more preferably 40C% or more, particularly preferably 50C% or more, even more preferably 60C% or more, and particularly preferably 70C% or more. The biomass ratio can be calculated by calculating the ratio of the carbon numbers of the raw materials derived from plants to the total carbon numbers of all the raw materials constituting the active energy ray curable resin composition, that is, the total carbon numbers of the polyol (a1), polyvalent isocyanate (a2), hydroxyl group-containing (meth)acrylate (a3), and ethylenically unsaturated monomer (B). In addition, a more accurate calculation method can be a measurement according to the method specified in ASTM D6866.
[0084] <Adhesive composition / adhesive> The active energy ray-curable resin composition of the present invention has adhesion to various members, and in particular has good adhesive strength when prepared into a pressure-sensitive adhesive, and can be applied to various applications such as coating agents, paints, inks, and pressure-sensitive adhesives. The pressure-sensitive adhesive composition of the present invention comprises the active energy ray-curable resin composition of the present invention, in other words, the use of the resin composition is specified as adhesion. The pressure-sensitive adhesive composition of the present invention is cured by irradiation with the above-mentioned active energy rays to prepare a very useful pressure-sensitive adhesive having good adhesive strength. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight. In addition, the number average molecular weight, weight average molecular weight, dispersity, glass transition temperature after curing, and gel fraction of the urethane (meth)acrylate compound were measured according to the above-mentioned methods, and the biomass ratio was calculated according to the above-mentioned methods.
[0086] As the polyol (a1), the following was prepared. "Priplast3199": Manufactured by CRODA, polyester polyol containing a structural portion derived from dimer acid (hydroxyl value 56.0 mgKOH / g, number average molecular weight 2004) "Priplast 1838": A polyester polyol containing a structural portion derived from dimer acid, manufactured by CRODA (hydroxyl value 60.0 mg KOH / g, number average molecular weight 1870) "Priplast3196": CRODA, polyester polyol containing a structural portion derived from dimer acid (hydroxyl value 37.0 mgKOH / g, number average molecular weight 3032)
[0087] [Preparation of urethane acrylate (A-1)] In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 74.66 parts of "Priplast3199" as polyol (a1), 16.56 parts of isophorone diisocyanate (IPDI) as polyvalent isocyanate (a2), 0.02 parts of 2,6-di-t-butyl-p-cresol as a polymerization inhibitor, and 0.06 parts of dibutyltin dilaurate as a reaction catalyst were added and reacted at 60° C. Next, 8.78 parts of 2-hydroxyethyl acrylate (HEA) (a3) were added to this system and reacted, and the reaction was terminated when the remaining isocyanate group became 0.1% or less, and a composition containing urethane acrylate (A-1) was obtained.
[0088] [Preparation of urethane acrylate (A-2)] In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 86.63 parts of "Priplast3199" as polyol (a1), 11.21 parts of isophorone diisocyanate (IPDI) as polyvalent isocyanate (a2), 0.02 parts of 2,6-di-t-butyl-p-cresol as a polymerization inhibitor, and 0.06 parts of dibutyltin dilaurate as a reaction catalyst were added and reacted at 60° C. Then, 2.16 parts of 4-hydroxybutyl acrylate (4HBA) (a3) were added to this system and reacted, and the reaction was terminated when the remaining isocyanate group became 0.1% or less, and a composition containing urethane acrylate (A-2) was obtained.
[0089] [Preparation of urethane acrylate (A-3)] In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 85.81 parts of "Priplast 1838" as polyol (a1), 11.9 parts of isophorone diisocyanate (IPDI) as polyvalent isocyanate (a2), 0.02 parts of 2,6-di-t-butyl-p-cresol as a polymerization inhibitor, and 0.06 parts of dibutyltin dilaurate as a reaction catalyst were added and reacted at 60° C. Next, 2.29 parts of 4-hydroxybutyl acrylate (4HBA) (a3) were added to this system and reacted, and the reaction was terminated when the remaining isocyanate group became 0.1% or less, and a composition containing urethane acrylate (A-3) was obtained.
[0090] [Preparation of urethane acrylate (A-4)] In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 90.3 parts of "Priplast 13196" as polyol (a1), 7.9 parts of isophorone diisocyanate (IPDI) as polyvalent isocyanate (a2), 0.02 parts of 2,6-di-t-butyl-p-cresol as a polymerization inhibitor, and 0.06 parts of dibutyltin dilaurate as a reaction catalyst were added and reacted at 60° C. Next, 1.8 parts of 4-hydroxybutyl acrylate (4HBA) (a3) were added to this system and reacted, and the reaction was terminated when the remaining isocyanate group became 0.1% or less, and a composition containing urethane acrylate (A-4) was obtained.
[0091] [Preparation of urethane acrylate (A'-1)] In a flask equipped with an internal thermometer, a stirrer, and a condenser, 16.3 parts of isophorone diisocyanate (IPDI) as polyvalent isocyanate (a2), 75 parts of "ADEKA New Ace V14-90" (ADEKA) as polyester polyol (a'1) not containing a structural portion derived from dimer acid, 0.02 parts of 2,6-di-t-butyl-p-cresol as a polymerization inhibitor, and 0.06 parts of dibutyltin dilaurate as a reaction catalyst were added and reacted at 60°C. Next, 8.65 parts of 2-hydroxyethyl acrylate (HEA) (a3) were added to this system and reacted, and the reaction was terminated when the residual isocyanate group became 0.1% or less, and a composition containing urethane acrylate (A'-1) was obtained.
[0092] [Table 1]
[0093] [Ethylenically unsaturated monomer (B)] As the ethylenically unsaturated monomers (B1), (B2) and (B3), the following were prepared. (B1-1) Isobornyl acrylate (Tg=97°C) (B1-2) Dicyclopentanyl acrylate (Tg=120°C) (B1-3) Cyclic trimethylolpropane formal acrylate (Tg=27°C) (B1-4) Tetrahydrofurfuryl methacrylate (Tg=60° C.) (B2-1) Tetrahydrofurfuryl acrylate (Tg=-12°C) (B2-2) n-Butyl acrylate (Tg=-56°C) (B3-1) Acryloylmorpholine (Tg=145°C) (B3-2) Isodecyl acrylate (Tg=-62℃)
[0094] <Example 1> [Preparation of active energy ray-curable resin composition] The urethane acrylate (A-1) and ethylenically unsaturated monomers (B1-4) and (B2-1) obtained above were mixed to obtain the composition shown in Table 2, and further, 4 parts of Omnirad 184 (manufactured by IGM RESINS) was mixed as a photopolymerization initiator per 100 parts of the urethane (meth)acrylate compound and the ethylenically unsaturated monomer, to obtain an active energy ray-curable resin composition. The adhesiveness of the obtained active energy ray-curable resin composition was evaluated as follows. The adhesiveness results are shown in Table 2 together with the biomass ratio.
[0095] [Adhesive strength] [Preparation of adhesive sheet for measuring adhesive strength] The obtained active energy ray-curable resin composition was applied to an easily-adhesive polyethylene terephthalate (PET) film (thickness 125 μm) using an applicator so that the film thickness after curing would be 100 μm, and the applied film was then irradiated with a tabletop UV irradiation device (manufactured by Eye Graphics, "Conveyor-type tabletop irradiation device") at 80 W / cm (high pressure mercury lamp) × 18 cmH × 1.9 m / min × 3 Pass (cumulative irradiation amount 2,400 mJ / cm 2 ) and cured to obtain an adhesive sheet for adhesive strength measurement.
[0096] [Test Method] The obtained adhesive sheet for adhesive strength measurement was cut into 25 mm x 100 mm, and then pressed onto a stainless steel plate (SUS304BA plate) as an adherend by rolling it back and forth twice using a 2 kg rubber roller under an atmosphere of 23°C and 50% relative humidity to prepare a test specimen. After leaving the test specimen in the same atmosphere for 30 minutes, a 180° peel test was performed at a peel speed of 0.3 m / min to measure the adhesive strength (N / 25 mm).
[0097] <Examples 2 to 8 and Comparative Examples 1 to 5> The same procedure was carried out as in Example 1, except that the polyol (a1), the polyisocyanate (a2), the hydroxyl group-containing (meth)acrylate (a3), the ethylenically unsaturated monomers (B-1) to (B-3), and the types and amounts of the reaction catalyst were changed as shown in Tables 2 and 3, to obtain an active energy ray-curable resin composition. The adhesiveness of the obtained active energy ray-curable resin composition was evaluated in the same manner as in Example 1. The adhesiveness results are shown in Tables 2 and 3 together with the biomass ratio.
[0098] [Table 2]
[0099] [Table 3]
[0100] From the results in Table 2 above, the active energy ray-curable resin compositions of Examples 1 to 8 contained urethane acrylate obtained using polyester polyol having a structural portion derived from dimer acid, and were environmentally friendly, while having good adhesive strength when prepared into an adhesive. In contrast, as shown in Table 3, in the active energy ray-curable resin compositions of Comparative Examples 1 to 5, in which the glass transition temperatures of the cured products were outside the range specified in the present invention, the adhesive strength was poor when the adhesive was prepared. [Industrial Applicability]
[0101] The active energy ray-curable resin composition of the present invention is suitable for environmental compatibility, and at the same time, has good adhesive strength when prepared into a pressure-sensitive adhesive, and can be suitably used for various applications such as coating agents, paints, inks, and pressure-sensitive adhesives.
Claims
1. a urethane (meth)acrylate compound (A) which is a reaction product of a polyester polyol (a1) containing a structural portion derived from a dimer acid, a polyisocyanate (a2) and a hydroxyl group-containing (meth)acrylate (a3), and has a number average molecular weight of 1,500 to 23,000; Ethylenically unsaturated monomer (B) An active energy ray-curable resin composition comprising: The active energy ray-curable resin composition, characterized in that the glass transition temperature of the cured product (I) of the active energy ray-curable resin composition is higher than 30°C and 70°C or lower.
2. The active energy ray-curable resin composition according to claim 1, characterized in that the polyester polyol (a1) containing a structural portion derived from a dimer acid has a number average molecular weight of 800 to 5,000.
3. 3. The active energy ray-curable resin composition according to claim 1, wherein the polyisocyanate (a2) contains at least one selected from the group consisting of aliphatic polyisocyanates and alicyclic polyisocyanates.
4. The active energy ray curable resin composition according to any one of claims 1 to 3, characterized in that the ethylenically unsaturated monomer (B) contains an ethylenically unsaturated monomer (B1) having a glass transition temperature of 0°C or more and 130°C or less, and an ethylenically unsaturated monomer (B2) having a glass transition temperature of -60°C or more and less than 0°C.
5. The active energy ray-curable resin composition according to any one of claims 1 to 4, further comprising a photopolymerization initiator (C).
6. A pressure-sensitive adhesive composition comprising the active energy ray-curable resin composition according to any one of claims 1 to 5.
7. A pressure-sensitive adhesive obtained by curing the pressure-sensitive adhesive composition according to claim 6.
Citation Information
Patent Citations
Resin composition for pressure-sensitive adhesive
JP1993043636A
Ethylenically-terminated urethane oligomer, coated optical fiber and preparation thereof
JP1993262848A
Urethane prepolymer, its production and pressure-sensitive adhesive containing the same as component
JP1998330453A
Printing plate for printing machine and tacky material for fixing the same
JP2003082059A
Urethan(METH)acrylate composition and sealant
JP2010100711A